2008
DOI: 10.1007/s11095-008-9561-z
|View full text |Cite
|
Sign up to set email alerts
|

Intra and Inter-Molecular Interactions Dictate the Aggregation State of Irinotecan Co-Encapsulated with Floxuridine Inside Liposomes

Abstract: Long-range interactions between irinotecan, floxuridine and excipients modulate the aggregation state of irinotecan, allowing for simultaneous release of both drugs from the liposomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…IRN in the external buffer is then able to cross the liposome bilayer and become protonated. IRN within the liposomes that is positively charged (pKa = 8.1) interacts with FOA that is negatively charged (pKa = 2.4) and probably forms a complex [36]. …”
Section: Resultsmentioning
confidence: 99%
“…IRN in the external buffer is then able to cross the liposome bilayer and become protonated. IRN within the liposomes that is positively charged (pKa = 8.1) interacts with FOA that is negatively charged (pKa = 2.4) and probably forms a complex [36]. …”
Section: Resultsmentioning
confidence: 99%
“…However, through thorough understanding of interactions among excipients and drugs, drug distribution inside nanoparticles, and properties of nanoparticle components in relation to their biofate and drug release mechanism, it is possible to engineer nanocarrier to meet the goals. For example, Dicko et al studied the drug-drug and drug-excipient molecular interactions that drive the co-loading process and coordinated release of irinotecan and floxuridine from the liposomal formulation CPX-1 [71]. To co-encapsulate drugs at the desired ratio, irinotecan was loaded via the neutral active antiport by exchanging its proton with triethanolamine buffer across the liposomal membrane, whereas floxuridine was passively loaded into the liposome.…”
Section: Technical Challenges and Limitationsmentioning
confidence: 99%
“…To co-encapsulate drugs at the desired ratio, irinotecan was loaded via the neutral active antiport by exchanging its proton with triethanolamine buffer across the liposomal membrane, whereas floxuridine was passively loaded into the liposome. Examinations using fluorescence, NMR and UV-V is revealed that the interplay between copper gluconate buffer and drugs limited the aggregate formation of irinotecan, allowing for slow release of irinotecan together with floxuridine from the liposomes [71]. …”
Section: Technical Challenges and Limitationsmentioning
confidence: 99%
“…Productspecific characterization focuses on drug-excipient interaction, drug loading mechanisms, drug-drug interactions, and physical disposition of the drug in the carrier. An example was presented where data from two characterization techniques were used to help determine the final drug product formulation (48). CPX-1 (irinotecan/floxuridine) liposome injection is a clinical stage liposomal nanomedicine intended for the treatment of advanced colorectal cancer.…”
Section: Liposomes: D Cabral-lillymentioning
confidence: 99%